(untitled) (Indian Journal of Public Health Research & Development, 2023)
To evaluate pre and post treatment results based on Laryngeal mucosal changes as assessed by direct video laryngoscopy/stroboscopy using Belafsky scores. In our study we have evaluated laryngeal changes in patients with dysphonia and RSI 10 before treatment and after 6 months of treatment with Tab. Pantoprazole and Tab. Mosapride. This prospective study was carried out on 50 patients attending the ENT out patient department of a tertiary care referral centre over a period of 18 months i.e. from Nov 2008 to Apr 2010. The study showed that prolonged therapy is required to treat laryngopharyngeal reflux (LPR) effectively and 24 h ambulatory dual probe pH metry and videolaryngoscopy to assess RFS are the most preferred diagnostic tools in LPR. Dr Speech software for voice analysis can give an objective assessment of voice changes in LPR before and after treatment. The treatment consisting of proton pump inhibiter (PPI) and prokinetic drugs proved to be effective in laryngopharyngeal reflux disease as improvement was seen in all the parameters including reflux findings score. According to results of our study, 24 h ambulatory dual probe pH-metry, Reflux Finding Score (RFS), can be used as indicators of efficacy of treatment.